Measurement of the Higgs boson production rate in association with top quarks in final states with electrons, muons, and hadronically decaying tau leptons at $$\sqrt{s} = 13\,\text {TeV} $$ - (:unkn) unknown (My University, 2021)
The rate for Higgs ($${\mathrm{H}} $$) bosons production in association with either one ($${\mathrm{t}} {\mathrm{H}} $$) or two ($${\mathrm{t}} {{\overline{{{\mathrm{t}}}}}} {\mathrm{H}} $$) top quarks is measured in final states containing multiple electrons, muons, or tau leptons decaying to hadrons and a neutrino, using proton–proton collisions recorded at a center-of-mass energy of $$13\,\text {TeV} $$by the CMS experiment. The analyzed data correspond to an integrated luminosity of 137$$\,\text {fb}^{-1}$$. The analysis is aimed at events that contain $${\mathrm{H}} \rightarrow {\mathrm{W}} {\mathrm{W}} $$, $${\mathrm{H}} \rightarrow {\uptau } {\uptau } $$, or $${\mathrm{H}} \rightarrow {\mathrm{Z}} {\mathrm{Z}} $$decays and each of the top quark(s) decays either to lepton+jets or all-jet channels. Sensitivity to signal is maximized by including ten signatures in the analysis, depending on the lepton multiplicity. The separation among $${\mathrm{t}} {\mathrm{H}} $$, $${\mathrm{t}} {{\overline{{{\mathrm{t}}}}}} {\mathrm{H}} $$, and the backgrounds is enhanced through machine-learning techniques and matrix-element methods. The measured production rates for the $${\mathrm{t}} {{\overline{{{\mathrm{t}}}}}} {\mathrm{H}} $$and $${\mathrm{t}} {\mathrm{H}} $$signals correspond to $$0.92 \pm 0.19\,\text {(stat)} ^{+0.17}_{-0.13}\,\text {(syst)} $$and $$5.7 \pm 2.7\,\text {(stat)} \pm 3.0\,\text {(syst)} $$of their respective standard model (SM) expectations. The corresponding observed (expected) significance amounts to 4.7 (5.2) standard deviations for $${\mathrm{t}} {{\overline{{{\mathrm{t}}}}}} {\mathrm{H}} $$, and to 1.4 (0.3) for $${\mathrm{t}} {\mathrm{H}} $$production. Assuming that the Higgs boson coupling to the tau lepton is equal in strength to its expectation in the SM, the coupling $$y_{{\mathrm{t}}}$$of the Higgs boson to the top quark divided by its SM expectation, $$\kappa _{{\mathrm{t}}}=y_{{\mathrm{t}}}/y_{{\mathrm{t}}}^{\mathrm {SM}}$$, is constrained to be within $$-0.9< \kappa _{{\mathrm{t}}}< -0.7$$or $$0.7< \kappa _{{\mathrm{t}}}< 1.1$$, at 95% confidence level. This result is the most sensitive measurement of the $${\mathrm{t}} {{\overline{{{\mathrm{t}}}}}} {\mathrm{H}} $$production rate to date.